Respuesta del cultivo de la naranjilla (Solanum quitoense) a la aplicación de fertilizantes foliares orgánicos, fertilizantes foliares sintéticos y 2,4-D Ester butílico: La Maná-Ecuador. 2010 - Vásquez Guaña, Edith Maritza (2012)
In the country there is very little information on the cultivation of naranjilla, especially in fertilization, the latest research being a Manual of Organic Agriculture INIAP Naranjilla by the year 2010. Small farmers in the canton La Maná, Pucayacu Parish, Precinct Esmeraldas, in recent years have been devoted to implement a new crop as naranjilla, which has adapted favorably by geographic and climatic conditions enabling them to provide fresh fruit to various national markets. Prior to venture into these markets, the fruit had to pass rigorous quality tests, with favorable results, but the product marketing companies, have suggested that they seek alternatives to the traditional use of chemicals so that it can continue to decrease its use.